STRUCTURAL HIERARCHIES OF MINERALS BASED ON BOND TOPOLOGY - Sokolova E.V.; Hawthorne F.C. (My University, 2003)
Two- and three-dimensional nets are widely used to describe and systematize crystal structures based solely on tetrahedral oxyanions. This approach may also be used to advantage for crystal structures based on polymerization of tetrahedra and octahedra. Thus, the [[6]M2[4]T2Φ12] sheet occurs as a fragment in a wide variety of structures, including silicate, phosphate, and sulfate minerals and several uranium minerals related to metaautunite, Ca[(UO2)(PO4] 2(H2O)6; sulfohalite, Na6[(SO4)2]FCl; natisite, Na2[TiO(SiO4)]; garnet, form [MΦ11-14], M = Na, Ca; Φ = O, OH, F, Cl, are common in a group of alkali sulfates and phosphates (and silicates) and occur in sulfohalite, Na6(SO4)2 FCl; galeite, Na15(SO4)5F4Cl; schairerite, Na21(SO4)7F6Cl; kogarkoite, Na3(SO4)F; arctite, (Na5Ca)Ca6 Ba(PO4)6F3; quadruphite, Na14 CaMgTi4[Si2O7]2[PO4] O4F2; polyphite, Na17Ca3Mg(Ti,Mn) 4[Si2O7]2(PO4) 6 O2F; and sobolevite, Na11(Na,Ca)(Mg,Mn)Ti4 [Si2O7]2(PO4)4 O3 F3. Bond valence considerations suggest that Si analogues of some of these structures should be stable, and several phases of tricalcium silicate, Ca3(SiO4)O, contain such trimeric clusters. These topological similarities between chemically and paragenetically diverse mineral structures are an important step in the eventual development of structural hierarchies that are based on bond topology (rather than chemical composition).